Evaluating Agricultural Economists within Colleges and Faculties of Agriculture. (30th December 2016) - Ker, Alan P.
Abstract : There is an increasing tendency for individual faculty evaluations, in whole or in part, to be done outside the department. Historically, this was not true. College committees acted only to uphold standards, ensure equity, and monitor procedural correctness within a department's evaluation process. Deans tended not to participate in routine faculty evaluations. Financial metrics like return on investment were not calculated on an individual faculty basis. Incentives from all administrative levels tended to be consistent with disciplinary success. These are no longer true for many agricultural economics departments. Both department and faculty responses have been mixed. At the department level, some have not responded while others have embraced a life science model. At the individual faculty level, some have not responded while others have chased money, impact factors, and publication counts. I explore the consequences of these changes for agricultural economists in a college dominated by life sciences with two caveats. First, this is an opinion article and represents my perceptions of general tendencies; there exist many exceptions in either direction. Second, I have biases which are undoubtedly reflected throughout. Il y a une tendance croissante aux évaluations individuelles des professeurs, en tout ou en partie. Ces évaluations sont réalisées de l'extérieur du département. Historiquement, ce n′était pas vrai. Les comités des collèges agissaient uniquement pour respecter les normes, assurer l′équité et surveiller l'exactitude procédurale au sein du processus d′évaluation d'un département. Les doyens universitaires ont tendance à ne pas participer aux évaluations routines de la faculté académique. Les statistiques financières, comme le rendement du capital investi, n'ont pas été calculées individuellement au niveau de la faculté. Les mesures incitatives de tous les niveaux administratifs ont tendance à être liées avec la réussite dans le domaine en question. Ceci n'est plus vrai pour de nombreux départements d'économie agricoles universitaires. Les réponses des départements et du corps professoral ont été mitigées. Au niveau départemental, certains n'ont pas répondu alors que d'autres ont adopté le modèle des sciences de la vie. Au niveau de la faculté individuelle, certains n'ont pas répondu alors que d'autres ont chassé de l'argent, des facteurs d'impact et une quantité de publication. J'explore les conséquences de ces changements pour les économistes agricoles dans un collège dominé par les sciences de la vie. Je souligne deux mises en garde. Premièrement, il s'agit d'un article d'opinion et représente ma perception des tendances générales; Il existe de nombreuses exceptions dans les deux directions. Deuxièmement, j'ai des préjugés qui seront reflétés tout au long.